Medical and Infectious Complications Associated with Pyelonephritis among Pregnant Women at Delivery. (28th September 2013) - Dotters-Katz, Sarah K.; Heine, R. Phillips; Grotegut, Chad A.
Abstract : Objective . Pyelonephritis is a common cause of antepartum admission and maternal morbidity. Medical complications associated with pyelonephritis during delivery are not well described; thus the objective of this study was to estimate medical, infectious, and obstetric complications associated with pyelonephritis during the delivery admission. Study Design . We conducted a retrospective cohort study using the Nationwide Inpatient Sample (NIS) for the years 2008–2010. The NIS was queried for all delivery-related discharges. During the delivery admission, the ICD-9-CM codes for pyelonephritis were used to identify cases and were compared to women without pyelonephritis. A multivariable logistic regression model was constructed for various medical, infectious, and obstetric complications among women with pyelonephritis compared to women without, while controlling for preexisting medical conditions and demographics. Results . During the years 2008–2010, there were 26, 397 records with a diagnosis of pyelonephritis during the delivery admission, for a rate of 2.1 per 1000 deliveries. Women with pyelonephritis had increased associated risks for transfusion, need for mechanical ventilation, acute heart failure, pneumonia, pulmonary edema, acute respiratory distress syndrome, sepsis, acute renal failure, preterm labor, and chorioamnionitis, while controlling for preexisting medical conditions. Conclusions . Pyelonephritis at delivery admissions is associated with significant medical and infectious morbidity.